Kerjasama Sekolah Teknologi Menengah dengan Industri melalui Pendidikan Sistem Ganda - Isnandar Isnandar (Universitas Negeri Malang, 2016)
This research was designed to identify cooperations implemented by Secondary School of Technology (STM) and industrial enterprises and to explore problems faced in the cooperation. In this cross sectional survey, the sample consisted of 10 out of 21 Secondary Schools of Technology (STM) implementing dual system of education in East Java. Data were collected by a questionnaire and interviews and then analyzed statistically in percentage measures. It was concluded that the planning of cooperations in the dual system of education included administrative, academic, and curricular aspects. In general, implementation of the planning was good enough, but there were so many problems faced by those participated in the dual system of education